Post Draw Effects of Prize Bonds’ Investment on Bullion Returns - Rabbani, Malik Ghulam Shabbir; Butt, Babar Zaheer (Public Finance Quarterly, 2021)
The study was conducted with the view to test the impact of cash out flow from the Pakistan Prize Bond market to Gold and Silver markets as a result of the bonds’ draw. The data from July 2007 to June 2019 was selected, which included Returns of Gold and Silver Markets. The data was tested with Event Study and AR, AAR & CAR were calculated. The results of AR & CAR did not endorse both the hypotheses on the basis that significant readings were found both in pre and post draw dates, to rule out any impact of cash flow from Prize Bond market into Gold and Silver markets. Whereas, AAR results were insignificant as such, hence fortifying the inference of rejection of both the hypotheses. So, both the hypotheses of having different returns on prize bond draw dates in Gold and Silver markets were not supported. Though the results were incongruent with the hypotheses, yet study outcomes as such are significant enough to propose regulators to contemplate legislations to fetch more funds from this comparatively cheaper source through enhanced documentation, which ultimately would make the economy more compliant.